Determination of the inflow time of maximum floods in a dam - Ana María Solis-Encarnación; Claudia Rojas-Serna (Revista Facultad de Ingeniería Universidad de Antioquia)
A methodology is proposed for the determination of the maximum floods entering a dam based on the analysis of different regression relationships between parameters characterized and identified from the maximum floods of a cascade dam system. It is possible to know the behavior of the inflow time of the maximum floods to a dam, taking as an application case the El Caracol dam in the Balsas river basin in Mexico. The characterization of the hydrographs made it possible to define models that provide advanced knowledge of the maximum flows and the time at which they will enter the dam, thus offering a model for forecasting maximum floods in a dam system.